The use of guided imagery to improve listening comprehension skills of Grade 6 pupils - Rachelle Abucejo; Jewett Boton; Joey Carlo L Doysabas (Davao Research Journal)
The prevalent issue of inadequate listening comprehension skills in elementary education, especially in English language learning, underscores the need for innovative instructional methods. This study explored the effectiveness of guided imagery in improving the listening comprehension of sixth-grade students at San Rafael Elementary School. The research instruments' validity and reliability were confirmed using the Aiken's V coefficient method and Cronbach's alpha, with scores of 0.83 and 0.77, respectively. A quasi-experimental design was used, with 30 students practicing guided imagery (experimental group) and another 30 following traditional teaching methods (control group) Pre-test scores for both groups fell below K-12 expectations. However, post-test results showed the experimental group’s mean score increased from 67.33 to 92.45, outperforming the control group’s rise from 66.45 to 78.88. These findings highlight the significant impact of guided imagery on listening skills and recommend its integration into teaching practices to enhance educational outcomes across subjects.